2020
DOI: 10.1039/d0ta02496a
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient overall water splitting ruthenium-cobalt alloy electrocatalyst across a wide pH range via electronic coupling with carbon dots

Abstract: Through the modification of the surface and bulk electronic structures of Ru, the developed Ru-based catalyst presents superior electrocatalytic hydrogen and oxygen evolution activities with great durability over a wide pH range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 46 publications
1
58
0
Order By: Relevance
“…Previous literatures have shown that by changing the electronic structure of Ru, RuCo alloy can exhibit better OER activity. 36,38,40 At the same time, related literature has also proven that the rich metal-insulator interface structure is benecial to improve the OER activity of Ru. 37,39 Therefore, it is hoped that both the Mott-Schottky effect will improve the charge transfer rate and the alloying will also optimize the electronic structure of Ru.…”
Section: Introductionmentioning
confidence: 95%
“…Previous literatures have shown that by changing the electronic structure of Ru, RuCo alloy can exhibit better OER activity. 36,38,40 At the same time, related literature has also proven that the rich metal-insulator interface structure is benecial to improve the OER activity of Ru. 37,39 Therefore, it is hoped that both the Mott-Schottky effect will improve the charge transfer rate and the alloying will also optimize the electronic structure of Ru.…”
Section: Introductionmentioning
confidence: 95%
“…Nevertheless, relatively little work has been performed on RuCo alloys, which have been reported to be useful in applications, such as but not limited to batteries 23 and Fischer-Tropsch catalysts 24,25 in addition to electrocatalysts for the hydrogen evolution reaction (HER), 22,[26][27][28][29][30] the hydrogen oxidation reaction (HOR), 31 the oxygen reduction reaction (ORR), 32,33 and the oxygen evolution reaction (OER). 34 Results for RuCo alloys used as electrocatalysts have been especially promising, with the alloys frequently outperforming the Pt standards at lower overall costs. Specically, a study which compared RuM (M ¼ Co, Ni, Fe) catalysts for the HOR, HER, ORR, and OER reported that the RuM alloys achieved higher activities for HOR and HER versus both pure Ru and Pt standards.…”
Section: Introductionmentioning
confidence: 99%
“…However, metallic Co has poor HER catalytic activity due to its weak hydrogen bonding energy [26–28] . In contrast, the noble metal ruthenium (Ru) is an ideal HER catalysts, with the cost of Ru being approximately 1/3 that of Pt [29–31] . However, the strong interaction between Ru and H atoms reduces the efficiency of H 2 desorption, slowing the overall HER kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] In contrast, the noble metal ruthenium (Ru) is an ideal HER catalysts,w ith the cost of Ru being approximately 1/3 that of Pt. [29][30][31] However,t he strong interaction between Ru and Ha toms reduces the efficiency of H 2 desorption, slowing the overall HER kinetics.T he incorporation of Ru atoms into aC omatrix could lessen the hydrogen bonding strength of Ru, thus promoting faster water adsorption/activation and optimizing Ha dsorption/H 2 desorption. [32] Alloying Co with Ru therefore is expected to deliver ac atalyst with excellent performance for both HER and the hydrolysis of AB,t hus offering two routes for hydrogen production.…”
Section: Introductionmentioning
confidence: 99%